The definition of the political system of the Roman Empire during the principate period: historiography of the problem - Efremenko, Ivan A. (Journal of the Belarusian State University. History, 2025)
This article analyses the historiographical study of one of the key issues in the political history of the Roman Empire. For over a century, historians have debated how to define the political system of the Roman Empire in the first two centuries AD. The solution to this problem was closely linked to changes in the methodological foundations of historical science and its approach to the study of historical sources. In the second half of the 19th and first half of the 20th centuries, historians, guided primarily by a positivistic approach, debated the essence of imperial power in the Roman Empire within the framework of the binary opposition between monarchy and republic. In the second half of the 20th century, many new approaches emerged in historical science: the theory of practices, the history of concepts, and poststructuralism, which, in turn, opened up vast expanses in the study of the political history of the Roman Empire. Using new methods, historians began to study the practices of political decision-making in the empire, the symbolic side of politics, language, and many other phenomena that had previously remained in the shadows. As a result of the debate about the nature of the principate system (monarchical or republican), historians came to the understanding that the principate was a specifically ancient form of political organisation, not reducible to a monarchy or a republic.
Keywords: historiography; Roman Empire; Octavian Augustus; emperor; principate